2014
DOI: 10.1128/ec.00060-14
|View full text |Cite
|
Sign up to set email alerts
|

A Large Nonconserved Region of the Tethering Protein Leashin Is Involved in Regulating the Position, Movement, and Function of Woronin Bodies in Aspergillus oryzae

Abstract: The Woronin body is a Pezizomycotina-specific organelle that is typically tethered to the septum, but upon hyphal wounding, it plugs the septal pore to prevent excessive cytoplasmic loss. Leashin (LAH) is a large Woronin body tethering protein that contains highly conserved N-and C-terminal regions and a long (ϳ2,500-amino-acid) nonconserved middle region. As the involvement of the nonconserved region in Woronin body function has not been investigated, here, we functionally characterized individual regions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Woronin bodies were visualized by expressing the fusion protein AoHex1‐EGFP (Figure c). In accordance with the previous studies (Han et al, ; Maruyama et al, ), Woronin bodies were tethered to septa at both sides near the pore in wild type and in normal septa in Δ glpA (Figure c). On the other hand, morphologically abnormal septa in Δ glpA had aberrant tethering of Woronin bodies (Figure c).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Woronin bodies were visualized by expressing the fusion protein AoHex1‐EGFP (Figure c). In accordance with the previous studies (Han et al, ; Maruyama et al, ), Woronin bodies were tethered to septa at both sides near the pore in wild type and in normal septa in Δ glpA (Figure c). On the other hand, morphologically abnormal septa in Δ glpA had aberrant tethering of Woronin bodies (Figure c).…”
Section: Resultssupporting
confidence: 92%
“…Therefore, using actin‐related gene ontology and BLAST‐based selection, we identified a novel Pezizomycotina‐specific gelsolin‐like protein GlpA and characterized its function. Aspergillus oryzae was selected in this study as a representative of Pezizomycotina species, since septal pore regulation has been extensively characterized by an experimental technique of quantitatively analyzing the ability to protect the adjacent cells upon hyphal wounding and by microscopic observation of the septum‐localizing proteins (Bleichrodt et al, ; Escaño et al, ; Han, Jin, Maruyama, & Kitamoto, ; Huang, Maruyama, & Kitamoto, ; Maruyama, Escaño, & Kitamoto, ; Maruyama et al, ; Tsukasaki, Saeki, Katayama, Maruyama, & Kitamoto, ). We have shown that GlpA is required for proper septum formation frequency, normal septum morphology and septal pore function by participating in CAR assembly and constriction.…”
Section: Introductionmentioning
confidence: 99%
“…Cold Spring Harbor Laboratory Press on June 7, 2019 -Published by genome.cshlp.org Downloaded from accordingly, the possibility to identify nonconserved yet functional proteins arouses strong opinions (The ENCODE Project Consortium 2012; Graur et al 2013;Han et al 2014). Available online tools for visualization of ribosome profiling data are listed in Table 2. Evidence at the protein level Mass spectrometry (MS)-based proteomics has emerged as the gold standard technique to assess the protein landscape of a cell or tissue and thus can offer additional evidence beyond ribosome profiling Mann 2003, 2016;Vogel and Marcotte 2012;Huttlin et al 2015).…”
Section: Human Genes Are Multicodingmentioning
confidence: 99%
“…8). 11,15,31) We cloned the Aohex1 gene, which encodes a protein constituting the Woronin body, and determined that the AoHex1 multimer is formed in peroxisomes and plays an essential role in survival against catastrophic cell injury. 32) It is important to note that the septal pore is not constitutively open and that fluctuations between the open-closed state is dependent on the behavior of the AoSO protein in response to environmental stress.…”
Section: )mentioning
confidence: 99%